การวิเคราะห์ต้นทุนคุณภาพสำหรับโรงงานหล่อโลหะ - กังวาน ชยุติมันต์กุล (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This thesis aims of find the quality cost and to study the expenses incurred in factory by examining the part of casting manufacture that uses electric furnaces and by emphasizing the part of capital that results from maintaining the quality of products. This is expected to become the guidelines for industry of the same kind. According to a study of present circumstances in the model factory, the researcher found that the factory serious problems concerning the quality of their products, including work returned by customers, overlapping work and repairing work during the process of manufacture. These could cause great expenses in connection with the quality of the products. Quality cost was one of the financial evaluators used the as an indicator and could help the staff to realize the effects of maintaining the quality of the products, which includes a great loss of income. The quality cost analysis process started with the analysis of expenses incurred the separation of different types of activities and expense, and the organization of the quality cost system, respectively. This included making forms to collect data used for calculation, staff training in data collection, quality cost calculation, and reporting the results. This led to a quality cost analysis according to each product being studied. The results obtained from the research process were that the factory could develop a quality cost system in order to understand the capital used in connection with quality system, to be able to better manage quality control and to evaluate real costs as an indicator. Regarding the model, the researcher found that the original cost was 35.82 bath/kilogram, quality cost was 8.22 bath/kilogram or 22.95%. The difference in cost was 3.06 bath/kilogram. This hidden cost was calculated as 8.54%